Incarceration on Trial: The Imprisonment of Paul and Silas in Acts 16 - Smith, Abraham (Journal of Biblical literature, 2021)
Scholarship on prisons and prison scenes in Acts has clarified the materiality of ancient prisons, the mythical structure of prison-release scenes, and the literary function(s) of the specific scenes in which Paul was a prisoner. Working with a narrow view of violence as only a physical and direct act of harm, though, scholars generally have not explored Luke's use of prisons as a part of a broader juridical nexus through which Luke amplifies the tyranny of violence faced by Acts' protagonists. Thus, to secure a broader conceptualization of violence, I initially review the work of recent philosophers and sociologists. Informed with an expanded view of violence, I then reread the account of the imprisonment of Paul and Silas in Acts 16 as a part of Luke's broader strategic objectives: (1) the aforementioned amplification of violence; (2) the interrogation of incarceration as both a physical and a social harm; and (3) the demystification of the xenophobia that Jesus's prophetic movement likely faced and tried to overcome.